Do School Principals Respond to Increased Public Scrutiny? New Survey Evidence from Australia1. (22nd April 2018) - Coelli, Michael; Foster, Gigi; Leigh, Andrew
Abstract : We explore responses of Australian school principals to the introduction of test score reporting via the My School website in 2010. Theory suggests that heightened public scrutiny should motivate principals to adopt best practices for improving their schools' test results. We use responses from both public and private schools to a custom‐built questionnaire administered to principals before (2009) and after (2012) the My School website launch. We find scarce evidence of meaningful adjustments over time, but we do find evidence of significantly different policies and practices across school groups.